Fostering Creativity in Intercultural and Interdisciplinary Teams: The VICTORY Model - Tang, Min (Frontiers in Psychology, 2019)
Teams are pervasive in the history of mankind. Particularly in our fast-growing modern society, teams composed of members from different cultures and disciplines are quite often used at workplace. Though widely used, the effectiveness of teams is inconsistent. Meta-analyses show a double-edged effect of diversity on creativity and innovation, suggesting that diversity needs to be tactfully managed if we want to leverage the creative potential of teams. The current paper strives to meet this challenge and makes suggestions on how to foster creativity in intercultural and interdisciplinary teams. It discusses the concepts of teams vs. groups and creativity vs. innovation. Drawing upon the sociocultural theories of creativity and innovation, particularly literature reviews and meta-analyses, this paper attempts to identify motivational, cognitive and environmental enablers of team creativity. These enablers can be summarized as a VICTORY model, which focuses on team (T) and synthesizes the sociocultural (Vision), motivational (Openness, Risk-taking, Yes-mindset) and cognitive (Ideation, Combination) antecedents of team creativity.